PENGARUH PENGGUNAAN MEDIA VISUAL (PIRAMIDA) TERHADAP HASIL BELAJAR MURID MATERI RANTAI MAKANAN DIKELAS V SEKOLAH DASAR - Podungge, Shafira Khairunissa; Meylan Saleh; Rifda Mardian Arif; Kudus; Nurfadliah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of using Visual Learning Media (Pyramid) on the learning outcomes of fifth-grade students at SDN 75 Kota Tengah, Gorontalo City. The study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The population consisted of all fifth-grade students at SDN 75 Kota Tengah, Gorontalo City, with a sample of 18 students. Data were collected through observation, tests, and documentation. The results revealed that the mean pretest score was 43.06, while the mean posttest score increased to 83.61. The posttest mean score was substantially higher than the pretest mean score, indicating an improvement in students’ learning outcomes after the implementation of the visual learning media. Hypothesis testing was conducted using SPSS version 26.0 through the Wilcoxon Signed-Rank Test (non-parametric test). The results showed an Asymp. Sig. (2-tailed) value of 0.000, which was lower than the significance level of 0.05. Therefore, it can be concluded that there was a statistically significant difference between the pretest and posttest scores of the experimental group. These findings indicate that the use of Visual Learning Media (Pyramid) had a significant positive effect on the learning outcomes of fifth-grade students at SDN 75 Kota Tengah, Gorontalo City.